Analisis Kegagalan Produk Baut Pengikat Pada Unit Fuel Pump Kendaraan Roda Dua - Sutiana; Simanjuntak, Edward (CV. Multi Kreasi Media, 2025)
Gasoline engine vehicles are vehicles that use 2 fuels, namely air and gasoline. In this test, it was observed that the fuel pump fastening bolt was damaged. This damage needs to be analyzed and examined to determine the cause of the damage to the fastening bolt component. The methods used to research bolt components include visual inspection, fractography, hardness testing, and Finite element method analysis using Solidworks software. From the results of the fractography test, it was determined that the damage to the bolt was caused by a torsional moment, leading to a fatigue fracture. The material used in the bolt component is ASTM A36. To validate the bolt material and determine the hardness value of the ASTM A36 material, a hardness test using the Vickers method was required, and the hardness results obtained for the ASTM A36 material were around 259.6 HV. The next test was to analyze the bolt to determine the torsional moment that occurred using the FEM method from the SolidWorks software. After the FEM test was carried out by providing a torque of 20 kgf on the bolt component, the bolt component broke due to holding an excessive load. Thus, the cause of damage to bolt components is due to excessive moment loads and material quality degradation.